Techniques in micromagnetic simulation and analysis. (31st July 2017) - Kumar, D; Adeyeye, A O
Abstract: Advances in nanofabrication now allow us to manipulate magnetic material at micro- and nanoscales. As the steps of design, modelling and simulation typically precede that of fabrication, these improvements have also granted a significant boost to the methods of micromagnetic simulations (MSs) and analyses. The increased availability of massive computational resources has been another major contributing factor. Magnetization dynamics at micro- and nanoscale is described by the Landau–Lifshitz–Gilbert (LLG) equation, which is an ordinary differential equation (ODE) in time. Several finite difference method (FDM) and finite element method (FEM) based LLG solvers are now widely use to solve different kind of micromagnetic problems. In this review, we present a few patterns in the ways MSs are being used in the pursuit of new physics. An important objective of this review is to allow one to make a well informed decision on the details of simulation and analysis procedures needed to accomplish a given task using computational micromagnetics. We also examine the effect of different simulation parameters to underscore and extend some best practices. Lastly, we examine different methods of micromagnetic analyses which are used to process simulation results in order to extract physically meaningful and valuable information.